1979
DOI: 10.2307/1936477
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Constraints on the Behavior, Morphology, and Community Structure of Anolis Lizards

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. A conceptual model of Anolis-habitat interactions is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
127
1
4

Year Published

1986
1986
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(135 citation statements)
references
References 43 publications
3
127
1
4
Order By: Relevance
“…Previous research has indicated that morphology and ecology are strongly correlated among Greater Antillean anoles (Moermond, 1979a;Losos, 1990a). Here, we have documented that this correlation continues to hold when Lesser Antillean taxa are added to the analysis.…”
Section: Lesser Antillean Speciessupporting
confidence: 65%
“…Previous research has indicated that morphology and ecology are strongly correlated among Greater Antillean anoles (Moermond, 1979a;Losos, 1990a). Here, we have documented that this correlation continues to hold when Lesser Antillean taxa are added to the analysis.…”
Section: Lesser Antillean Speciessupporting
confidence: 65%
“…For example, several anole species (ecomorphs) have convergently evolved similar morphology and habitat preferences, such as longer limbs being positively correlated with the lizards occurring on branches with larger diameter (Moermond, 1979;Williams, 1983). This correlation between habitat preference and limb length may result from decreased cylinder diameter having more severe detrimental effects on the sprinting speeds of the longer limbed species compared with shorter limbed species (Irschick and Losos, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Cadle & Greene, 1993), and its physical implications, is thought to strongly in¯uence the evolution of body form in vertebrates (e.g. Moermond, 1979;Miles & Ricklefs, 1984;Wikramanayake, 1990). Even in limbless, elongate vertebrates such as snakes, closely related species may be included in different morphological syndromes depending on which macrohabitat is explored (see e.g.…”
Section: Introductionmentioning
confidence: 99%